Us and Them: Distributional Preferences in Small and Large Groups - Heiner Schumacher; Iris Kesternich; Michael Kosfeld; Joachim Winter (Center for Economic Studies and ifo Institute (CESifo), 2014)
We analyze distributional preferences in games in which a decider chooses the provision of a good that benefits a receiver and creates costs for a group of payers. The average decider takes into account the welfare of all parties and has concerns for efficiency. However, she attaches similar weights to small and large groups so that she neglects large provision costs that are dispersed among many payers. This holds regardless of whether the decider benefits from the provision or not. A CES utility function which rationalizes average behavior implies altruism in bilateral situations and welfare-damaging actions when costs are dispersed.
Keywords: C91; D63; H00; 330; social preferences; distribution games; concentrated benefits and dispersed costs